Incidence of viral and fungal complications after utilization of alternative donor sources in hematopoietic cell transplantation. Issue 8 (21st July 2020) - Whited, Laura K.; Handy, Victoria W.; Hosing, Chitra; Chow, Eric
Abstract : Allogeneic hematopoietic cell transplantation (HCT) remains the only curable option for adult patients with hematologic malignancies. According to guidelines published by the American Society for Transplantation and Cellular Therapy, allogeneic HCT should be offered to all intermediate‐ and high‐risk patients with acute leukemia. While matched‐related donor (MRD) grafts continue to be the preferred stem cell source for allogeneic HCT, studies comparing MRD grafts to matched‐unrelated donor (MUD) grafts showed comparable outcomes in patients with acute leukemia. Unfortunately, for those without a suitable matched‐related graft, the probability of finding a suitable matched‐unrelated donor varies significantly depending on racial and ethnic background. With allogeneic HCT procedures increasing year after year due to the increased availability of suitable donors, each of these alternative donor sources merits special clinical considerations, specifically with regard to infections. Infections remain a significant cause of morbidity and mortality after allogeneic transplant, especially in those receiving alternative donor grafts. Due to the high‐risk nature associated with these donor grafts, it is important to understand the true risk of developing infectious complications. While there are a multitude of infections that have been described in patients post‐allogeneic HCT, this review seeks to focus on the incidence of cytomegalovirus (CMV) and invasive fungal infections (IFI) in adult patients receiving alternative donor source transplantation for hematologic malignancies.